Counterpossibles - Williamson, Timothy (Proceedings of the Amsterdam Colloquium, 2015)
According to orthodoxy, all counterpossibles (counterfactual conditionals with impossible antecedents) are true, or at least not false. Nevertheless, some counterpossibles look false. The problem is not just how best to tidy up an unimportant corner of the logic and semantics of counterfactuals. It has significant theoretical and methodological ramifications in several directions. This paper defends the orthodox view against some recent objections, and explains the most recalcitrant appearances to the contrary by our pre-reflective reliance on a fallible heuristic in the assessment of counterfactuals.